(untitled) (Perner’s Contacts, 2018)
This article deals with a functional calculation of the untyped reel of a working machine, which was renovated because of damage. This damage was occurred due to overload due to unspecified load. This fact can represent a certain degree of danger, because it is not possible to quantify the safe load area. Therefore, in the previous step the creation of the drawing documentation was created by measurement of real device. Based on this it is possible immediately to obtain all necessary parameters for a functional calculation. It will be the basis for feedback of analytical dimensional calculation in order to determine the maximal permissible value of the load mass on the given winding device.